The Relationship Between Hepatopulmonary Syndrome and Altitude. Issue 3 (2014) - Valley, Morgan A; Trotter, James F; Thomas, Deborah; Ginde, Adit A; Lowenstein, Steven R; Honigman, Benjamin
Abstract : BACKGROUND: In a previous small retrospective study, the authors reported that hepatopulmonary syndrome was less common among liver transplant candidates at high-altitude centres compared with low-altitude centres. OBJECTIVE: To further explore the relationship between hepatopulmonary syndrome and altitude of residence in a larger patient cohort. METHODS: A cohort of 65, 264 liver transplant candidates in the Organ Procurement and Transplantation Network liver database between 1988 and 2006 was analyzed. Hepatopulmonary syndrome diagnosis was determined during a comprehensive evaluation at a liver transplant centre by physicians who were experienced in the diagnosis and treatment of hepatopulmonary syndrome. The altitude of residence was determined for each patient by assigning the mean altitude of the zip code of residence at the time of entry on the wait list. Mean zip code elevation was calculated using the National Elevation Dataset of the United States Geological Survey, which provides exact elevation measurements across the entire country. RESULTS: Hepatopulmonary syndrome was significantly less common at higher resident altitudes (P=0.015). After adjusting for age, sex and Model for End-Stage Liver Disease score, there was a 46% decrease in the odds of hepatopulmonary syndrome with every increase of 1000 m of resident elevation (OR 0.54 [95% CI 0.33 to 0.89]). CONCLUSION: There was a negative association between altitude and hepatopulmonary syndrome. One plausible explanation is that the lower ambient oxygen found at higher elevation leads to pulmonary vasoconstriction, which mitigates the primary physiological lesion of hepatopulmonary syndrome, namely, pulmonary vasodilation.